Constructing Contributive Dialogue Between the Doctrine of God in John Owen Thought and First Principle of Pancasila - Christar Arstilo Rumbay (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2021)
Abstract. The doctrine of God contains of unending discussion and special characterized by trinity, the main doctrine of Christianity, holds specific character, lays on soteriology and relates to the work of redemption. Furthermore, it plays significantly as an antithesis to other faiths, as the consequence, this Christian identity being a subject of dialogue in interreligious society, even within believers’ circle. However, this topic encompasses surround disciplines, including, specifically speaking, socio-politics. In the other side, Pancasila, a state ideology of Indonesia, occupies the faith of its citizens by accommodating the humanity-divinity relationship in a very sensitive way. This academic work intends to supply alternative perspectives to theology and socio-politics tension. Specifically speaking, evaluates any possibilities of dialogue between the doctrine of God in John Owen Thought and the first principle of Pancasila. The result of this research suggests numerical code as the possibility of conversation between them.